SOME PROBLEMS ORIGINATED AT THE ENDEAVOUR FOR OBJECTIVE EVALUATION OF STUDENTS - MONKA, Peter; MONKOVÁ, Katarína (Trends in education, 2009)
The article deals with investigation of possibilities at increasing of objective examination of student examination and evaluation of student´s knowledges in educational process. There are specified some problems originated at the endeavour for objective evaluation of students in the article. The article is direct supported from grants KEGA no.3/5172/07 and KEGA no.3/5173/07 of Cultural and Educational Grant Agency of Ministry of Education of Slovak republic.
Keywords: examination; objective evaluation; key powers.